A Bifunctional Fluorescence Probe for the Detection of Hypochlorous Acid and Viscosity in Living Cells and Zebrafish - Xin Zhang; Yanmei Si; Xinpeng Chen; Xuqing Nie; Yiheng Zhang; Li Lin; Yehao Yan (Molecules)
As two significant indicators in the microenvironment, hypochlorous acid and viscosity play important roles in multitudinous physiological metabolic processes. However, it is challenging to determine the dynamic levels of hypochlorous acid and viscosity in living cells and organisms because of the absence of effective molecular tools that can simultaneously detect hypochlorous acid and viscosity in organisms. Herein, a molecular design strategy was presented to fabricate a single fluorescence probe that can simultaneously detect hypochlorous acid and viscosity by using two different emission channels. In JXR, TICT-based 4-(2-(5-(dimethylamino)thiophen-2-yl)vinyl)-1-methylpyridin-1-ium-iodide chromophore serves as energy acceptor in the FRET process and sensors for hypochlorous acid and viscosity. JXR showed a large Stokes shift, wide emission peak distance, high photostability, and low toxicity. JXR could detect hypochlorous acid and viscosity rapidly, sensitively, and selectively by emitting different fluorescence signals. Importantly, JXR was successfully applied to track the intracellular hypochlorous acid and viscosity in living cells. Meanwhile, the generation of endogenous hypochlorite in living cells can be observed by using JXR.